Motorcycle parts and aftermarket industry regional value chain in Southern Africa - Sithembiso Mtanga; Richard McCamel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper provides an overview of the structure, key functions, and characteristics of the motorcycle parts and aftermarket industries in Southern Africa in order to identify challenges to and opportunities for growth in these industries. The research examines the end markets and utilization of motorcycles, the status of these markets, and demand for local or regional production processes. The paper also considers the main factors affecting the sales of motorcycles and their parts in the region and assesses whether a more coordinated approach between governments and foreign and local firms could lead to assembly and/or manufacturing value-added activity in the Southern African Development Community region.
Keywords: F1; L5; O14; O25; 330; aftermarket; industrialization; motorcycles; motorcycle parts; regional integration; South Africa; SADC